EXPLORING THE RELATION BETWEEN HIGH CREATIVITY AND HIGH ACHIEVEMENT AMONG 8TH AND 11TH GRADERS - Bart, William M.; Can, Iclal; Hokanson, Brad (International Online Journal of Education and Teaching, 2020)
This study explores the relationship between high creativity and high scholastic achievement in mathematics, reading, and science among 8th and 11th grade students. A quantitative methodology was used in the study. Data were collected from 941 eighth-grade students and 605 eleventh-grade students at an independent public school district in Minnesota, a Midwestern State in the U.S.A. The data collection instruments included a general personal questionnaire, the Torrance Tests of Creative Thinking (TTCT) Figural Form A, and the Minnesota Comprehensive Assessment Test (MCA). Correlations were computed and chi-square analyses were performed to address research questions. Grade-based standard scores were used in the measurement of creativity and academic achievement with the top 20% cutoff scores being used to identify students with high achievement and students with high creativity. The results indicated that the relation between high creativity and high academic achievement varies among eighth and eleventh graders. High mathematics and high reading achievement are related to high creativity among both eighth- and eleventh-grade students, but with small effect sizes. High achievement in science is related to high creativity among eleventh-graders. Our results indicate that high creativity and high achievement in reading, mathematics, and science achievement tend to be positively related, but those relationships are at best weak, indicating that there are substantial components to high creativity that are not shared by high achievement in mathematics, reading, and science and vice versa. Keywords: creativity, academic achievement, eighth grade, eleventh grade